Mawaris Murtad Dalam Pandangan Hukum Islam dan Konvensional - Hikmal Rizky (Getpress Management Journals, 2025)
This study explores the legal implications of apostasy (murtad) on inheritance rights from both the perspective of Islamic law, as codified in the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI), and conventional law, as governed by the Indonesian Civil Code (KUHPerdata). Using a normative juridical approach through a library-based study, this research analyzes primary and secondary legal sources to examine the extent to which apostasy influences inheritance entitlement. The findings indicate a fundamental divergence between the two legal systems. Under KHI, apostasy constitutes a legal impediment to inheritance due to the religious incompatibility between the heir and the decedent, aligning with the classical fiqh view that prohibits inheritance across religious boundaries. In contrast, the Civil Code does not consider religious affiliation as a determinant in succession law; it upholds kinship as the primary basis of inheritance, thereby allowing apostates to inherit from or bequeath to their family members regardless of religious status. This legal disparity reflects a broader tension between the theological objectives of Islamic family law and the secular, pluralistic orientation of Indonesian civil law. The study underscores the need for legal harmonization or at least clearer jurisprudential guidance to resolve conflicts arising in multi-religious familial contexts.